2020
DOI: 10.1002/ange.202000406
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of Cationic Boron Complexes Distorted by Pyridine‐based Pincer Ligands: Isolation of a Photochemical Hofmann–Martius‐type Intermediate

Abstract: A family of cationic boron complexes was synthesized, using a dianilidopyridine pincer ligand, which imposes in‐plane distortion of the geometry at boron towards T‐shaped. Reactivity of these cations toward hydride and base was investigated, and the utility of these cations as precursors to a variety of π‐conjugated BN heterocycles was demonstrated. 300 nm irradiation of a deprotonated pincer boron complex triggered a C−N cleavage/C−C formation yielding a dearomatized boryl imine, which has a structure akin to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…[27,28] In fundamental terms, it is now evidently known that hydrogen bonds are formed in various X-HÁ Á ÁY systems, where the atoms X and Y are electronrich elements or more electronegative elements and Y possesses one or more lone pair, such as N, O, or F. [29][30][31][32][33] In line to this, specifically considering the interaction of water molecules with organic molecules, it is largely observed that hydrogen bonding interactions in pyridine, [34][35][36][37] pyrimidine, [38,39] and its derivatives play a significant role to drive their solvation dynamics and thus holds very high relevance in heterocyclic chemistry. [40,41] Large-scale industrial applicability of pyridine in the fine chemical [42,43] and pharmaceutical industries [44][45][46][47] as a solvent and reagent made its hydration properties a strong point of research interest among various researchers. In addition to this, a comprehensive understanding of hydrogen bonding interactions in pyridine is also essential for advances in the biochemical industries, ranging from designing receptors for basic amino acid side chain recognition [48] to chemometric probing of various biomolecules.…”
Section: Introductionmentioning
confidence: 99%
“…[27,28] In fundamental terms, it is now evidently known that hydrogen bonds are formed in various X-HÁ Á ÁY systems, where the atoms X and Y are electronrich elements or more electronegative elements and Y possesses one or more lone pair, such as N, O, or F. [29][30][31][32][33] In line to this, specifically considering the interaction of water molecules with organic molecules, it is largely observed that hydrogen bonding interactions in pyridine, [34][35][36][37] pyrimidine, [38,39] and its derivatives play a significant role to drive their solvation dynamics and thus holds very high relevance in heterocyclic chemistry. [40,41] Large-scale industrial applicability of pyridine in the fine chemical [42,43] and pharmaceutical industries [44][45][46][47] as a solvent and reagent made its hydration properties a strong point of research interest among various researchers. In addition to this, a comprehensive understanding of hydrogen bonding interactions in pyridine is also essential for advances in the biochemical industries, ranging from designing receptors for basic amino acid side chain recognition [48] to chemometric probing of various biomolecules.…”
Section: Introductionmentioning
confidence: 99%